Unveiling perspectives of Islam : seeing through the eyes of Singapore's educated Chinese youths who subscribe to No religion - Nur Ameera Amirrudin (2017)
This paper explores the views of Singaporean-Chinese university undergraduates with no religion on three themes namely violence and terrorism, gender relations, and Islamic practices as well as how these perceptions arise. Correlations of identities, gender, existing level of knowledge of Islam, and relationships with Muslim individuals with regards to attitudes towards Islam are examined. The importance of uncovering the dominant perspectives of Islam in Singapore comes with the rise of terrorist attacks worldwide as well as concerns of Islamophobia by Muslims living in the country. The results of 8 interviews illuminate the effectiveness of knowledge and education in reducing negative perceptions. The findings also show that respondents exercise their identity as a dominant ethnic group in maintaining societal norms resulting in unfavorable attitudes towards the out-group. Finally, while the negative perceptions of respondents are rather mild, these data reveal that actions should be taken to curb this negativity.